A novel approach for nonlinear bending response of macro- and nanoplates with irregular variable thickness under nonuniform loading in thermal environment. Issue 4 (4th July 2019) - Dastjerdi, Shahriar; Tadi Beni, Yaghoub
Abstract: A new method has been presented for static analysis of macro- and nano sector plates with variable thickness. The thickness variations are assumed linearly, functionally, and also irregularly. The governing equations have been derived based on the nonlocal modified higher-order shear deformation theory and have been solved applying the semi-analytical polynomial method. The obtained results have been compared with the results of the other relevant articles. The effective parameters on the analysis have been investigated such as the thickness, the size of the plate under uniform and nonuniform loadings, and the boundary conditions including free edges. Communicated by Marco Amabili.